Community-Based Educational Intervention to Enhance Higher Education Aspirations among Underprivileged Students - Rini Setiawati; Umi Rojiati (Smart Society, 2026)
Higher education plays an important role in improving quality of life and breaking the cycle of poverty. However, economic limitations often prevent underprivileged students from pursuing university education. This study aimed to enhance higher education aspirations among students from social assistance recipient families in Batu Putuk Village, Teluk Betung Barat District, Bandar Lampung City, Indonesia, using the Participatory Action Research (PAR) approach. The program involved educational socialization, motivational activities, academic mentoring, and university entrance examination preparation for 30 students from economically disadvantaged households. The results of the self-awareness questionnaire indicated a significant increase in students’ motivation toward higher education. Approximately 94% of participants expressed strong motivation to obtain better employment opportunities and reduce dependence on social assistance in the future, while 88% were determined to improve their family’s socioeconomic conditions. In addition, 94% of students reported increased family awareness regarding the importance of higher education. Scholarship opportunities and parental support were identified as major factors influencing students’ aspirations to pursue university education, each reported by 88% of participants. These findings highlight the importance of educational empowerment, accessible financial support, and cross-sector collaboration in increasing higher education participation among underprivileged students.